2014
DOI: 10.1186/preaccept-7863745011292633
|View full text |Cite
|
Sign up to set email alerts
|

Transient extracellular application of gold nanostars increases hippocampal neuronal activity

Abstract: Background: With the increased use of nanoparticles in biomedical applications there is a growing need to understand the effects that nanoparticles may have on cell function. Identifying these effects and understanding the mechanism through which nanoparticles interfere with the normal functioning of a cell is necessary for any therapeutic or diagnostic application. The aim of this study is to evaluate if gold nanoparticles can affect the normal function of neurons, namely their activity and coding properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…For instance, similar NP–neuron interactions were observed for negative carbon black, hematite iron oxide, titanium dioxide, 15 and gold NPs. 18 , 24 However, the interactions in those studies, unlike those reported in this work, were investigated over prolonged time exposure (from few hours to days) and at different concentration ranges within them. In this work, we have conducted a systematic study on different NP materials, of different size, shape composition, and coating, and we have investigated the immediate effects of NPs just after their administration, within the first few minutes and at a rather low-concentration range.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…For instance, similar NP–neuron interactions were observed for negative carbon black, hematite iron oxide, titanium dioxide, 15 and gold NPs. 18 , 24 However, the interactions in those studies, unlike those reported in this work, were investigated over prolonged time exposure (from few hours to days) and at different concentration ranges within them. In this work, we have conducted a systematic study on different NP materials, of different size, shape composition, and coating, and we have investigated the immediate effects of NPs just after their administration, within the first few minutes and at a rather low-concentration range.…”
Section: Discussionmentioning
confidence: 93%
“…For example, neurons cultured on multielectrode arrays (MEAs) exposed to carbon black (CB), hematite (Fe 2 O 3 ), and titanium dioxide (TiO 2 ) NPs display an acute, concentration-dependent alteration of spontaneous electrical activity. 15 An increased electrical excitability also occurs in mouse hippocampal slices exposed to star-shaped Au NPs, 18 an observation confirmed at the single neuron level by patch clamp recordings. 24 Moreover, as shown in another study, quantum dots (QDs) with a negative coating were preferentially internalized by neurons with respect to astrocytes, oligodendrocytes, or microglia, suggesting that the surface charge is critical for neuron-specific uptake.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…26 It has been reported that the nano-neuro interaction depolarizes neuronal membrane potential, resulting in increased excitability and firing rate of individual neurons. 40, 41 The increase in the excitability of the neurons results in increased probability of burst discharge instead of single firing event. 42 Consequently, in the present study, as a result of nanoparticle binding to a fraction of neurons in the neuronal network, the excitability of only the neurons tagged with nanoparticles is expected to increase.…”
Section: Discussionmentioning
confidence: 99%